RELIGIOSITY IN CHARLES DICKENS’ CHRISTMAS NOVELS A Study of Structural Genetic - Sitio, Robert Juni Tua; Rasid, Yumna; Rahmat, Aceng (IJLECR (International Journal of Language Education and Cultural Review), 2018)
The objective of this research was to understand comprehensively the meaning and existence of religiosity in Dickens’ Christmas Novels. It was a qualitative research by using structural genetic approach. The data were collected by using content analysis to classify the frequency of the concept or the code of the text. Then conducting them towards dimension of religiosity. The data analysis and interpretation indicates that (1) Dimensions of religiosity exist in intrinsic structures such theme, plot, character, setting indicate the importance of religiosity to make a better world. (2) Social structure indicates the gap between the rich and the poor in English society. (3) The author’s world view indicates man’s experience effect human character as religious or irreligious person. The findings lead to recommendation to practice literary research on religion and literature as well as motivate students gaining knowledge and good interpretation of the text and the context of religiosity.